Ethnobotanical survey of medicinal plants used as insects repellents in six malaria endemic localities of Cameroon - Roger Ducos Fokouo Youmsi; Patrick Valère Tsouh Fokou; Elisabeth Zeuko’o Menkem; Issakou Bakarnga-Via; Rodrigue Keumoe; Victor Nana; Fabrice Fekam Boyom (Journal of Ethnobiology and Ethnomedicine, 2017)
Abstract Background The combined efforts to combat outdoor/indoor transmission of malaria parasites are hampered by the emerging vector resistance in a wide variety of malaria-endemic settings of Africa and the rest of the world, stressing the need for alternative control measures. This study aimed at documenting insect’s repellent plant species used by indigenous populations of 6 localities of East, South, West and Centre regions of Cameroon. Methods Information was gathered through face-to-face interviews guided by a semi-structured questionnaire on the knowledge of medicinal plants with insect repellent properties. Results A total of 182 informants aged from 25 to 75 years were recruited by convenience from May to June 2015. The informants had general knowledge about insects’ repellent plants (78.6%). A total of 16 plant species were recorded as insects’ repellents with 50% being trees. The most cited plants were Canarium schweinfurthii (Burseraceae) (in four localities, 58/182), Elaeis guineensis (Arecaceae) (in three localities, 38/182), Chromolaena odorata (Compositae) (16/182) and Citrus limon (Rutaceae) (11/182) in two localities each. Among the repellent plant species recorded, 50% were reported to be burnt to produce in-house smokes, 31.2% were mashed and applied on the body, and 18.8% were hung in the houses. The leaf was the most commonly used plant part (52.9%), followed by the bark (17.6%). Conclusions This study has shown that rural populations of the 6 targeted localities possess indigenous knowledge on repellent plants that are otherwise cost-effective and better choice for repelling insects including malaria-transmitting mosquitoes. Meanwhile, such practices should be validated experimentally and promoted as sustainable malaria transmission control tools in the remotely located communities.